La Comprensión desde el marco de la Hermenéutica y su aproximación en la Filosofía de D. Davidson (2008)
The present article intends to analyze Davidson’s position regarding the relationship between aspeaker and an interpreter and his approach to Gadamer’s position, from such a seemingly distantposition as Hermeneutics. Despite differences in their positions, it is possible to find points in common.Those are the ones considered as key concepts included in the article.